Rh(iii)-catalyzed chelation-assisted intermolecular carbenoid functionalization of α-imino Csp3–H bonds. Issue 83 (4th September 2015) - Chen, Xun; Xie, Ying; Xiao, Xinsheng; Li, Guoqiang; Deng, Yuanfu; Jiang, Huanfeng; Zeng, Wei
Abstract : A Rh(iii )-catalyzed cross-coupling/cyclization cascade of α-imino Csp 3 –H bonds with donor/acceptor α-acyl diazocarbonyl compounds has been developed. Abstract : A Rh(iii )-catalyzed cross-coupling/cyclization cascade of α-imino Csp 3 –H bonds with donor/acceptor α-acyl diazocarbonyl compounds has been developed. This novel transformation involves ligand-directed Csp 3 –H bond functionalization with carbenoids under the pyridine-chelation assistance, and offered an efficient access to synthetically versatile polysubstituted N -(2-pyridyl)pyrroles with a broad range of functional group tolerance.